Macroeconomic uncertainty and private investment in Ghana: An empirical investigation - Bekoe, W.; Adom, P.K. (International Journal of Economics and Financial Issues, 2013)
In spite of the progress made in economic performance over the years, the Ghanaian economy continues to be bedevilled by a host of constraints. Among these constraints are low levels of savings and investments which have raised serious concerns among economists and policy makers with respect to the sustainability of the achievements attained so far. This study attempts to investigate empirically the link between investments and uncertainty using dataset from Ghana covering the period 1975 to 2008. In the empirical analysis, the paper aims at separating ordinary variability from uncertainty by the construction of measures of uncertainty for some key macroeconomic indicators and using them to assess their impact on investment behaviour within an econometric framework including other acceptable determinants of investment. The Phillip-Hansen cointegration test confirms the existence of long-run equilibrium relationship between private investment, standard determinants of investment, and macroeconomic uncertainty. Result from the study shows that on the whole the investment-uncertainty link reveals a significant negative effect of all macroeconomic uncertainty indicator variables on private investment with the exception of real exchange rate volatility. The values for price of capital uncertainty, real GDP growth uncertainty, and terms of trade uncertainty are large in absolute terms. The regression result further reveals that private investment displays important inertia and shows slow adjustment process towards long-run equilibrium. Lastly, the summary measure of macroeconomic uncertainty which encompasses the first principal components of the conditional variances of the five macroeconomic variables shows a consistent indirect effect on private investment. Generally we found macroeconomic uncertainties to be more detrimental to private investment growth in the long-run relative to the short-run. © 2013, Econjournals. All rights reserved.
Keywords: Fully modified ordinary least square technique; Ghana; Macroeconomic uncertainty; Partial adjustment model; Private investment behaviour